THE ECONOMIC VIABILITY OF AN AGROFORESTRY SYSTEM IN RELATION TO MONOCULTURE - Rodrigues Maia, Felipe (Journal of Interdisciplinary Debates, 2023)
This study investigated the economic viability of agroforestry systems (SAFs) compared to monoculture, focusing on the Brazilian context. The research used a literature review and analysis of recent studies to evaluate the environmental benefits and economic impacts of these systems. It was found that agroforestry systems contribute significantly to the conservation of biodiversity, the improvement of soil quality and carbon sequestration. Furthermore, crop diversification and community participation play crucial roles in promoting these sustainable practices. It is concluded that the transition to agroforestry systems is a promising choice for Brazilian farmers, promoting economic and environmental resilience. It is essential to invest in training, access to resources and favorable policies to overcome barriers to the adoption of these systems.